Effects of Hot and Cold Leaves Extracts of Azadirachta Indica on Xanthomonas Campestris - C. E. , Ejike; I. H. , Iheukwumere (African Journal of Education,Science and Technology (AJEST), 2017)
There is a worldwide interest in searching for safe and effective novel antibacterial compounds of plant origin for the control of plant pathogenic bacteria which is responsible for the great impact on the growth and productivity of agricultural crops. In this study, the effects of hot and cold leaf extracts of Azadirachta indica on Xanthomonas campestris was carried out. The organism was isolated from symptomatic pepper fruits and leaves using Yeast Dextrose Chalk Agar (YDCA). The isolate was characterized and identified using its colonial description, Gram staining and biochemical characteristics. The phytochemical constituents of the leaf extract of Azadirachta indica were determined quantitatively using spectrophotometeric method. The antibacterial activity of the leaf extracts was carried out using agar-well diffusion method. Tube dilution method was used to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using double-fold serial dilution at concentrations 31.25mg/ml to 500mg/ml. The phytochemical analysis of Azadirachta indica leaf extracts revealed the presence of tannins, flavonoid, alkaloids, steroids, cardiac glycosides, phenolics and saponins. The results of the present study revealed the pronounced activities of the leaf extracts against the tested organism, which differed significantly (p < 0.05) from ciprofloxacin. The activities of hot n-hexane (8.33mm), ethanolic (7.00mm), petroleum-ether (6.33mm) and aqueous (6.00mm) leaf extracts differed significantly (p < 0.05) from activities of cold ethanolic (22.67mm), n-hexane (20.67mm), petroleum-ether (19.33mm) and aqueous (8.33mm) leaf extracts. The results of the MICs and MBCs of the leaf extracts of Azadirachta indica showed that the cold extracts exhibited inhibitory and cidal activities against the organisms. This study recommends that cold extraction using organic solvents is suitable for studying the antibacterial activity of Azadirachta indica and Azadirachta indica leaf extracts could serve as alternative pesticide to plant diseases caused by Xanthomonas campestris.